Effect of Glomus manihotis inoculation and salt stress on antioxidant and biochemical properties of Chia (Salvia hispanica L.) - Salim, Mohamad Agus (Universitas Sebelas Maret, 2023)
Plant productivity is often constrained by abiotic stress in the form of high salt levels. However, a symbiosis between plant and arbuscular mycorrhizal fungi can reduce the severity of the effect of salt stress on cultivated plants. The aim of this study was to determine the impact of salt stress on the antioxidant substances and biochemical parameters of chia (Salvia hispanica L.) plants that had been inoculated with the fungus Glomus manihotis. A factorial completely randomized design with seven replicates was used with status of inoculation by the fungus G. manihotis (inoculated vs. not inoculated) as one of factors and the concentration of sodium chloride (NaCl) (0, 50, 100, and 200 mM) as the other status factor. Several parameters in the chia plants were measured including: root infection, phosphorus content, chlorophyll and carotenoid contents, antioxidant enzyme activities (superoxide dismutase and catalase), and malondialdehyde content. The results showed that chia plants inoculated with G. manihotis (mycorrhizal plants), even under salt stress conditions, had higher phosphorus content than non-mycorrhizal plants. High salt levels reduced the percentage of root infection by the mycorrhizal fungus of G. manihotis. Under salt stress conditions, chlorophyll and carotenoid contents of chia leaves were higher in mycorrhizal plants than in non-mycorrhizal plants. The activities of superoxide dismutase and catalase of mycorrhizal chia plants were higher than those of non-mycorrhizal plants, even though they were grown under conditions of high salt levels. The malondialdehyde content of chia plants increased with salt concentration, but decreased in chia plants inoculated with G. manihotis. The findings of this study indicate that G. manihotis inoculation is effective in reducing the effect of salt stress on chia plants.